KEKHUSUSAN BEBAN PEMBUKTIAN TERBALIK DALAM TINDAK PIDANA PENCUCIAN UANG (MONEY LAUNDERING) - Widya Wipramita, Cok Istri; Tuni Cakabawa L., Putu (Kertha Wicara : Journal Ilmu Hukum; Vol. 03, No. 01, Maret 2014)
This paper shall be entitled as “SPECIALTY REVERSE BURDEN OF PROOF IN MONEY LAUNDERING”. Money laundering is an extraordinary crime that the proof system using reverse burden of proof. Of proof systems are specific rules established by the government through the issuance of the provisions of Act No.8 of 2010 on Preention and Eradication of Proof in Money Laundering. There is norm conflict in the reversed burden of proof, as opposed to several articles in the criminal law and the principles of the verification system itself. So be used a normative study with the approach of legislation and comparison on the existing principles that can be unknown and deduced about settings as well as legal basis and validity appear reversed the burden of proof in Money Laundering in Indonesia.
Keywords: Inverted proof, Crime, Money laundering